Corydalis Saxicola Bunting Total Alkaloids Attenuate Walker 256-Induced Bone Pain and Osteoclastogenesis by Suppressing RANKL-Induced NF-κB and c-Fos/NFATc1 Pathways in Rats - Ju, Linjie; Hu, Peipei; Chen, Ping; Wu, Jiejie; Li, Zhuoqun; Qiu, Zhixia; Cheng, Jun; Huang, Fang (Frontiers in Pharmacology, 2021)
Metastatic bone pain is characterized by insufferable bone pain and abnormal bone structure. A major goal of bone cancer treatment is to ameliorate osteolytic lesion induced by tumor cells. Corydalis saxicola Bunting total alkaloids (CSBTA), the alkaloid compounds extracted from the root of Corydalis saxicola Bunting, have been shown to possess anticancer and analgesic properties. In this study, we aimed to verify whether CSBTA could relieve cancer induced bone pain (CIBP) and inhibit osteoclastogenesis. The in vivo results showed that CSBTA ameliorated Walker 256 induced CIBP and osteoporosis in rats. Histopathological changes also supported that CSBTA inhibited Walker 256 cell-mediated osteolysis. Further in vitro analysis confirmed that CSBTA reduced the expression of RANKL and downregulate the level of RANKL/OPG ratio in breast cancer cells. Moreover, CSBTA could inhibit osteoclastogenesis by suppressing RANKL-induced NF-κB and c-Fos/NFATc1 pathways. Collectively, this study demonstrated that CSBTA could attenuate cancer induced bone pain via a novel mechanism. Therefore, CSBTA might be a promising candidate drug for metastatic bone pain patients.